2017
DOI: 10.1016/j.memsci.2017.08.037
|View full text |Cite
|
Sign up to set email alerts
|

A low energy gravity-driven membrane bioreactor system for grey water treatment: Permeability and removal performance of organics

Abstract: Synthetic grey water was treated with a low-pressure gravity-driven membrane bioreactor (GDMBR) system. The system was operated without any direct shear at the membrane surface and without any cleaning or flushing. In order to reduce energy consumption, one reactor was operated without aeration and the results were compared with an aerated reactor. Although the dissolved oxygen content was low (0.4-0.6 mg/L) in the nonaerated system, a stable permeability was observed at a level of around 20 L/m 2 hbar (flux o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(33 citation statements)
references
References 62 publications
1
31
1
Order By: Relevance
“…As a result, consistent backwashing, flushing and cleaning are needed to achieve the targeted flux. Furthermore, the needs for pumps, control processes, pre‐treatment and supporting equipment are vital (Ding et al ., 2017). Moreover, the energy consumption and capital cost of MBRs are relatively high (Wurochekke et al ., 2016).…”
Section: Greywater Treatment Technologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, consistent backwashing, flushing and cleaning are needed to achieve the targeted flux. Furthermore, the needs for pumps, control processes, pre‐treatment and supporting equipment are vital (Ding et al ., 2017). Moreover, the energy consumption and capital cost of MBRs are relatively high (Wurochekke et al ., 2016).…”
Section: Greywater Treatment Technologiesmentioning
confidence: 99%
“…It is called greywater because the water turns to grey colour when it is stored without any treatment (Chaillou et al ., 2011). Generally, 70% domestic wastewater is regarded as greywater (Ding et al ., 2017). It has the great potential to recycle and reuse due to very low concentration of organic pollutants content compare with the combined household wastewater.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis revealed that carefully planned potable water reuse projects should be able to provide a level of protection from waterborne illness and chemical contaminants comparable to (and, in some cases, better than) the level of protection the public experiences in many drinking water supplies across the nation. However, researchers [11] pointed out that the analysis was presented as an example and should not be used to endorse certain treatment schemes or to determine the risk at any particular site without site-specific analysis [7,9,11,33,[48][49][50][51][52][53].…”
Section: Figure 4 Relative Risk Shown On a Logarithmic Scale Posedmentioning
confidence: 99%
“…Therefore, recycling bath wastewater in university campuses as a research object is of great importance. At present, different physical treatments [ 13 , 14 ], chemical treatments [ 15 , 16 ], biological treatments [ 17 , 18 , 19 ], membrane methods and composite methods [ 20 , 21 ] have been adopted to treat bathing wastewater, such as coagulation, filtration, adsorption [ 22 , 23 ], membrane filters [ 24 , 25 , 26 , 27 ], electrocoagulation–flotation [ 28 ] and UV disinfection [ 29 ].…”
Section: Introductionmentioning
confidence: 99%